2020
DOI: 10.1039/d0ra05083k
|View full text |Cite
|
Sign up to set email alerts
|

Label-free single-molecule identification of telomere G-quadruplexes with a solid-state nanopore sensor

Abstract: Nanopore detection of single-molecule G-quadruplexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…These G4 structures induced different blocking currents while translocation through CDM-Nanopore. Also, G4 structures would reversibly fold and melted dynamically in the confined nanopore environment. In addition, the translocations of λ-DNA molecules demonstrate that the capture rate increased significantly after the addition of formamide into DNA translocation experiments with CDM-Nanopore, as shown in Figure S7.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These G4 structures induced different blocking currents while translocation through CDM-Nanopore. Also, G4 structures would reversibly fold and melted dynamically in the confined nanopore environment. In addition, the translocations of λ-DNA molecules demonstrate that the capture rate increased significantly after the addition of formamide into DNA translocation experiments with CDM-Nanopore, as shown in Figure S7.…”
Section: Resultsmentioning
confidence: 98%
“…The telomere sequences (5′-(AG 3 T 2 )­4–3′) were chosen to assess the molecular detection performance of the proposed CDM-Nanopore with G4 structures. According to the previous work of our group, we knew that the telomere sequence spontaneously formed a highly ordered secondary structure in the presence of some ions, called G4. The G4 structures with a small size of 24 bp were used to verify the sensitivity of the fabricated CDM-Nanopore. According to the formula calculation with eq 1, the pore diameter we used for molecular detection was ∼3.8 nm.…”
Section: Resultsmentioning
confidence: 99%
“…[ 73‐74 ] Lately, Wang and coworkers reported a label‐free approach for the detection of inter‐, intra‐, and tandem molecular G‐quadruplexes in different cation buffers with solid‐state nanopores, and used the method to monitor the folding process of single‐molecule G‐quadruplexes. [ 75 ] Li and coworkers used an α ‐HL nanopore to analyze the interaction between a G‐quadruplex structure formed by the human telomere sequence and a small molecule ligand, pyridostatin (PDS), revealing that PDS could promote the folding and stability of G‐quadruplex structures. [ 76 ] In addition, translocation studies demonstrated that PDS and K + have a synergistic effect on the stability of G‐quadruplex structures when simultaneously bound to one G‐quadruplex (Figure 11).…”
Section: Analysis Of Biomolecular Structuresmentioning
confidence: 99%
“…As a powerful single-molecule platform, nanopore has played an important role in DNA sequencing, sensing of various biomolecules, detection of cancer cells, , evaluation of enzyme activity, ion detection, and analysis of DNA and RNA secondary structure. In particular, α-hemolysin (α-HL) nanopores possess a natural advantage for capturing and analyzing folded structures because of their large nanocavity volume (∼40 nm 3 ) . To date, α-HL has successfully identified the characteristics of DNA secondary structures that are challenging to observe by bulk measurements. , For example, Gu et al studied the two-tetrad G-quadruplex adopted by the thrombin-binding aptamer captured within the α-HL vestibule and the unraveling of its kinetics upon binding with different cations .…”
Section: Introdutionmentioning
confidence: 99%